Multiple Roles of Peripheral Immune System in Modulating Ischemia/Hypoxia-Induced Neuroinflammation - Guo, Liang; Zhu, Lingling (Frontiers in Molecular Biosciences, 2021)
Given combined efforts of neuroscience and immunology, increasing evidence has revealed the critical roles of immune system in regulating homeostasis and disorders of central nervous system (CNS). Microglia has long been considered as the only immune cell type in parenchyma, while at the interface between CNS and the peripheral (meninges, choroid plexus, and perivascular space), embryonically-originated border-associated macrophages (BAMs) and multiple surveilling leukocytes capable of migrating into and out of the brain have been identified to function in the steady state. Hypoxia-induced neuroinflammation is the key pathological procedure that can be detected in healthy people at high altitude or in various neurodegenerative diseases, during which a very thin line between a beneficial response of the peripheral immune system in maintaining brain homeostasis and a pathological role in exacerbating neuroinflammation has been revealed. Here, we are going to focus on the role of peripheral immune system and its crosstalk with CNS in the steady state and especially in hypobaric or ischemic hypoxia-associated neuroinflammation.